Investment in infrastructure and Peruvian economic development (1997 – 2020) (LACCEI, 2024)
The objective of the research was to determine the relationship between fixed investment in infrastructure and Peruvian economic development during the period from 1997 to 2020. To this end, the research was quantitative, correlational and of non-experimental design, using public statistical sources and the subsequent application of the non-parametric statistic Kendall's rank coefficient. The results found allow us to conclude that fixed investment in infrastructure (engineering contribution) has a strong relationship with economic development taking into account its social (GNI index), economic (PIB per capita) and humanistic (HDI) components.